A new giant Atractus (Serpentes: Dipsadidae) from Ecuador, with notes on some other large Amazonian congeners - Schargel, Walter E.; Lamar, William W.; Passos, Paulo; Valencia, Jorge H.; Cisneros-Heredia, Diego F.; Campbell, Jonathan A. (Zootaxa, 2013)
We describe a new species of Atractus from Cordillera de los Guacamayos in the Andes of Ecuador. This new species is the largest known species of Atractus, reaching almost 120 cm in total length with a robust habitus. We also use multivariate statistical analyses of morphometric data to look into the taxonomic confusion involving other large, banded/blotched, species of Atractus in Western Amazonia. We show that A. snethlageae has a widespread distribution in Amazonia and has been repeatedly confused with A. major in Ecuador owing to its color polymorphism. Our multivariate statistical analyses support previous suggestions to recognize A. snethlageae as a distinct species relative to A. flammigerus. Taxonomic accounts are provided for both A. major and A. snethlageae including detailed color pattern descriptions. We also find that there are no valid morphological differences to support recognizing A. arangoi as a separate species from A. major; consequently we synonymize the former name with the latter.